Deciphering functional landscape and clinical implications of enhancer RNAs in lung adenocarcinoma - Aike Li; Liguang Zhang; Xinsheng Du; Yi Dong; Yan Guo; Jiwei Zhao; Xiuli Fang; Pingping Lin (Scientific Reports)
Abstract Lung adenocarcinoma (LUAD) is a common and deadly subtype of lung cancer with high mortality and limited treatment options. Enhancer RNAs (eRNAs) have emerged as important regulators in cancer biology, but their specific roles in LUAD have not been fully explored. This study aimed to investigate the role of eRNAs in LUAD pathogenesis and evaluate their potential as diagnostic biomarkers and therapeutic targets. Through integrated bioinformatics and experimental approaches, we identified differentially expressed eRNAs associated with LUAD progression. Functional analysis demonstrated that these eRNAs regulate critical pathways related to cell growth, division, repair, immune response, and tumor development. We constructed eRNA-centric regulatory networks, elucidating their interactions with transcription factors, enhancer-promoter loops, and RNA-binding proteins. Notably, eRNA ENSR00000188682 was highlighted for its central role, along with its associated transcription factor and downstream target gene ADRB2. Additionally, we developed a diagnostic prediction model based on eRNA expression profiles, which showed promising diagnostic accuracy. Our findings provide a comprehensive understanding of eRNA-mediated regulation in LUAD and suggest that eRNAs hold significant potential as prognostic biomarkers and therapeutic targets for improved clinical outcomes.